Haemostatic, inflammatory and haematological biomarkers among orthopaedic patients with prolonged immobilisation and hypercoagulable risk - Ramli, Noor Nabila (2024)
Venous thromboembolism is a major public health concern due to its high incidence of morbidity and mortality. Patients who experienced lower limb/s trauma with prolonged immobilisation will induce the hypercoagulable state that finally contributes to the VTE development. Therefore, this study aims to evaluate the changes in hypercoagulable markers (haemostatic, inflammatory and haematological) and clinical risk factors (gender, age, type of injury, BMI and smoking status) in prolonged immobilised orthopaedic trauma patients and hypercoagulable risk. This is a prospective cohort study of prolonged immobilised orthopaedic trauma patients admitted to the orthopaedic ward at Hospital Universiti Sains Malaysia from August 2020 to March 2022. A total of 54 patients with lower limb/s fractures, ages ranging from 11 to 50 years old, who required immobilisation for more than 5 days without receiving anticoagulant prophylaxis were involved in this study. The laboratory tests included D-dimer, fibrinogen, PT, aPTT, free protein S, protein C, antithrombin, CRP, ESR and platelet count were serially measured on day 1 and day 5 of immobilisation. Meanwhile, clinical risk factor that include gender, age, type of injury, BMI and smoking status were recorded during the admission. The paired t-test analysis demonstrated that several biomarkers gave a significant mean difference between day 1 and day 5 of immobilisation, which included fibrinogen, protein C, antithrombin, CRP, ESR and platelet count. The mean differences increased for each biomarker with fibrinogen was increased by 0.66g/L (p<0.001), protein C was increased by 14.07% (p<0.001), antithrombin was increased by 11.67% (p<0.001), ESR was increased by 17.98mm/hr (p<0.001), and platelet count was increased by 128.59×109/L (p<0.001) on day 5 of immobilisation. On the contrary, the mean difference for CRP decreased by 19.53mg/L (p=0.022) on day 5 of immobilisation. There was a significant moderate positive correlation between the CRP parameter with D-dimer (Pearson correlation, r =0.45, p=0.002), fibrinogen (r =0.53, p<0.001) and PT (r =0.42, p=0.005). On the other hand, ESR parameters showed a moderate positive correlation with D-dimer (r =0.40, p=0.003), strong positive correlation with fibrinogen (r =0.75, p<0.001) and moderate positive correlation with aPTT (r =0.38, p=0.005). Among the abnormal parameters (fibrinogen, protein C, antithrombin, CRP, ESR and platelet count) observed in this study, only protein C showed a significant association with age (31-40) and smoking status. In conclusion, this study found several biomarkers (fibrinogen, ESR, and platelet count) that showed significant changes after day 5 of immobilisation. Even though there was no VTE incident documented in this study, previous studies have shown that these biomarkers are prothrombic parameters that show the body's response towards tissue injury following trauma. Thus, these biomarkers are probably useful in assessing the risk of VTE related to hypercoagulable state and could support prophylaxis indications against VTE in a high-risk patient in the case of trauma immobilisation.